LANGUAGE SEPARATION IN TELETANDEM: WHAT CORPUS ANALYSIS CAN TELL US - de Lima-Lopes, Rodrigo E.; Aranha, Solange [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2023)
The purpose of this paper is to investigate 16 Initial Teletandem Oral Sessions (iTOS) within Teletandem Brasil Project to verify if the participants rely on language separation, one of the principles adopted by tandem learning. We focus on the lexical choices Brazilian students learning English as a Foreign Language, and US (non-Brazilian) citizens learning Portuguese as a Foreign Language make during their conversation. Data are from MulTeC (Multimodal Teletandem Corpus) and the lexical choices in each language segment were manually classified using wordlists and Keyword in Context and ANOVA tests were calculated across the sessions. Results show that the language separation principle tends to be respected and that Brazilians and non-Brazilians continue speaking the target language during the sessions; however, they also use a myriad of resources to maintain communication. This article contributes to the study of teletandem, primarily by quantitively analysing the linguistic data of initial sessions thus making it possible to understand some of the participants’ strategies to overcome their linguistic difficulties.
Keywords: Corpus Linguistics; Initial Teletandem Oral Sessions (iTOS); Learner Corpora; Separation of languages principle